2001
DOI: 10.1080/01468030151073010
|View full text |Cite
|
Sign up to set email alerts
|

Loss Behavior of Single-mode Optical Fiber Microbend Sensors

Abstract: Periodic microbending has been studied to develop an insight into the loss behavior of single-mode microbend sensors by using the finite-difference beam propagation method. Loss sensitivity variations with wavelength are examined, as well as the optical loss dependence on the number of microbends and the modal field perturbations caused by the microbending.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Both multimode and single-mode fibers have been used for the constructions of these sensors [19]. While multimode microbend sensors show the maximum sensitivity when the bending frequency is equal to the difference in propagation constants for the propagating and radiation modes [20], in single-mode optical fiber microbend sensors, the maximum sensitivity is achieved when the spatial bend frequency equals the difference between the propagation constants of the fundamental mode and a discrete cladding mode [21].…”
Section: Microbend Structurementioning
confidence: 99%
“…Both multimode and single-mode fibers have been used for the constructions of these sensors [19]. While multimode microbend sensors show the maximum sensitivity when the bending frequency is equal to the difference in propagation constants for the propagating and radiation modes [20], in single-mode optical fiber microbend sensors, the maximum sensitivity is achieved when the spatial bend frequency equals the difference between the propagation constants of the fundamental mode and a discrete cladding mode [21].…”
Section: Microbend Structurementioning
confidence: 99%
“…JW Berthold [11] has analyzed the micro-bending properties of gradient multimode fiber and stepped multimode fiber in 1995, And used to measure vibration, stress and temperature and other environmental parameters. In 2001, G. Murtaza et al Analyzed the microbending properties of ordinary single-mode fiber analyzed by finite difference beam propagation method, and analyzed the loss characteristics of micro-bend fiber optic sensor [12]. FIGURE 6.…”
Section: Figure 5 Schematic Diagram Of the In-fiber Transmission Micmentioning
confidence: 99%
“…Micro-bend fiber vibration sensor is a kind of early study of the vibration sensor [11][12], its working principle shown in Figure 6. Wherein the micro-bend deformer consists of two corrugated plates having a specific period, the period of which is determined by the propagation constant between the fiber modes.…”
Section: Figure 5 Schematic Diagram Of the In-fiber Transmission Micmentioning
confidence: 99%
See 2 more Smart Citations